The efficacy of gabapentin in reducing pain intensity and postoperative nausea and vomiting following laparoscopic cholecystectomy: A meta-analysis - Wang, Lifeng; Dong, Yucai; Zhang, Jiling; Tan, Hongwu (Medicine (Baltimore), 2017)
It is unknown whether gabapentin is effective in reducing acute pain following laparoscopic cholecystectomy. The purpose of the current meta-analysis was to evaluate the efficacy of gabapentin in reducing pain intensity and postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy. All randomized controlled trials (RCTs) evaluating the efficacy of gabapentin in reducing pain intensity and PONV after laparoscopic cholecystectomy were searched on the following databases: PubMed, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), the Google database, the Chinese Wanfang database, and the China National Knowledge Infrastructure (CNKI). The most recent literature search was conducted on March 21, 2017. Outcomes including visual analog scale (VAS) at 12 and 24 hours, total morphine consumption, and the occurrence of PONV. Continuous outcomes were expressed as the weighted mean difference (WMD) and 95% confidence interval (CI), and the one discontinuous outcome was expressed as risk ratio (RR) and 95% CI. Stata 12.0 software was used for meta-analysis. A total of 9 studies involving 966 patients were identified. In total, there were 484 gabapentin subjects and 482 controls. Compared with the control group, gabapentin was associated with lower VAS at 12 hours (WMD = -10.18, 95% CI: -17.36 to -2.80, P = .007) and 24 hours (WMD = -6.33, 95% CI: -8.41 to -4.25, P = .000), which was equivalent on a 110-point VAS scale to 10.18 points at 12 hours and 6.33 points at 24 hours. Compared with the control group, gabapentin was associated with less total morphine consumption by approximately 110.83 mg (WMD = -110.83, 95% CI: -183.25 to -38.42, P = .003). In addition, the occurrence of nausea and vomiting in gabapentin was decreased (25.2% vs 47.6, RR = 0.53, 95% CI: 0.44-0.63, P = .000). Gabapentin was efficacious in reducing postoperative pain, total morphine consumption, and morphine-related complications following laparoscopic cholecystectomy. In addition, there was a negative correlation between the gabapentin dosage and the occurrence of nausea and vomiting. The number of included studies is limited, and more studies are needed to verify the effects of gabapentin in laparoscopic cholecystectomy patients.